Determinação multirresíduo de agrotóxicos em milho empregando método QuEChERS modificado e LC-MS/MS - Facco, Janice de Fátima (2017)
Corn is a cereal used in human and animal food, and moreover, as a source of raw material for other by-products, acquiring global importance. By presenting a distinct centesimal composition when compared with others cereals, the residue analysis becomes more complex, requiring methods and tools more efficient to reach the objective. This study has as goal the validation of a modified QuEChERS method employing a clean-up step with freezing out and EMR-Lipid sorbent with determination by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). In this method, different classes of pesticides in different levels of concentration were evaluated. The method was validated for 45 pesticides with recovery and RSD results between 70 and 120% and ≤ 20%, respectively. The method limits of detection and quantification were 3 to 30 μg kg-1 and 10 to 100 μg kg-1, respectively. The proposed method was applied in real samples, including whole and broken corn seed, corn flour and popcorn in order to evaluate the performance. In the analyzed samples, carbendazim and fipronil were found in a unique sample in concentrations below method LOQ. The proposed method showed to be efficient for the determination of pesticide residues in corn samples.